2022
DOI: 10.1155/2022/5397032
|View full text |Cite
|
Sign up to set email alerts
|

Safety Risk Evaluation of Large and Complex Bridges during Construction Based on the Delphi‐Improved FAHP‐Factor Analysis Method

Abstract: With the increase in construction scale and difficulty of large and complex bridges in China, it has become increasingly difficult to assess the safety risks of bridges during the construction period. Therefore, how to reasonably assess the safety risk of large, complex bridges during construction has become particularly important. Existing assessment methods are subjective in assigning weights, and it is difficult to select representative important factors to focus on for the prevention and control of numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The WBS-RBS (work breakdown structure-risk breakdown structure) can systematically organize the risk patterns of projects [20], which facilitates risk planning response, data processing, and experience accumulation. However, at the same time, it cannot be well integrated with temporal and spatial changes.…”
Section: The Safety Risk Identification Methods Based On the G-t-wbs-...mentioning
confidence: 99%
See 1 more Smart Citation
“…The WBS-RBS (work breakdown structure-risk breakdown structure) can systematically organize the risk patterns of projects [20], which facilitates risk planning response, data processing, and experience accumulation. However, at the same time, it cannot be well integrated with temporal and spatial changes.…”
Section: The Safety Risk Identification Methods Based On the G-t-wbs-...mentioning
confidence: 99%
“…Aliyari et al [19] carried out a preliminary risk analysis of a bridge with the help of UAVs. Ji et al [20] constructed the safety risk evaluation system of bridge engineering based on the WBS-RBS analysis method. Zhang et al [21] constructed the safety risk evaluation system of deep foundation pit projects based on the WBS-RBS analysis method, also.…”
Section: Introductionmentioning
confidence: 99%
“…Xing et al [ 9 ] assessed the impact of various pile driving techniques and grouting methods on the mechanical properties of rock-socketed piles. Ji et al [ 10 ] based on the Yinzhou Lake Bridge project, identified sources of risk within divisional work and conducted risk prioritization. Li et al [ 11 ] constructed evaluation models to assess the construction safety risks of highway bridges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This method proves its practicality and efficiency in analyzing and evaluating multi-hazard risks for bridges. Ji et al 13 introduced a large-scale risk assessment method for complex bridge structures based on Delphi-enhanced Fuzzy Analytic Hierarchy Process (FAHP) factor analysis. The approach was validated through a comparative study with practical engineering cases and the Analytic Hierarchy Process, confirming its feasibility and practicality.…”
Section: Introductionmentioning
confidence: 99%